Design of a budgetary technique for agroindustrial microenterprises of food, located in Sogamoso, based on the characterization of each one of them (2013)
The activities of man, from his creation to the present day, have revolved around the economic roblem manifested in a continuous struggle for his survival and development. This situation has placed him as an agent that produces or consumes, through individual decisions that, obviously,generate processes that affect the whole society. Hence, microenterprises as a factor of social development, determine the way as people and society seek to meet efficiently both the individual and collective needs It is important to solve a growing number of needs through the use of productive, scarce or limited resources, which have different uses. In this process, technical decisions are involved, which determine at any given time, the classes of goods to be produced and distributed to satisfy personal,group or social needs. It follows from the above that an agroindustrial microenterprise that has not designed a budget system, will be at a disadvantage to those that have established it. Indeed, the budget allows quantifying in monetary terms and in advance, the result of decisions and of different goals, so that it effect on the organization can be visualized to serve as a tool to facilitate management control, in order to achieve greater effectiveness and efficiency in operations.